Microbiome-Assisted Breeding to Understand Cultivar-Dependent Assembly in Cucurbita pepo - Kusstatscher, Peter; Adam, Eveline; Wicaksono, Wisnu Adi; Bernhart, Maria; Olimi, Expedito; Müller, Henry; Berg, Gabriele (Frontiers in Plant Science, 2021)
Recently it was shown that long-term plant breeding does not only shape the plant characteristics, but also impacts the plant-associated microbiota substantially. This requires a microbiome-integrative breeding approach, which was not yet shown. Here, we investigate this for the Styrian oil pumpkin (Cucurbita pepo L. subsp. pepo var. styriaca Greb.) by analyzing the microbiome of six genotypes (the complete pedigree of a three-way cross hybrid, consisting of three inbred lines and one open pollinating cultivar) in the seed and rhizosphere as well as the progeny seeds. Using high-throughput amplicon sequencing targeting the 16S rRNA and the ITS1 genes, the bacterial and fungal microbiomes were accessed. Seeds were found to generally carry a significantly lower microbial diversity compared to the rhizosphere and soil as well as a different microbial composition, with an especially high fraction of Enterobacteriaceae (40-83%). Additionally, potential plant beneficial bacterial taxa, including Bacillaceae, Burkholderiaceae and Pseudomonadaceae were found to be enriched in progeny seeds. Between genotypes, more substantial changes can be observed for seed microbiomes compared to the rhizosphere. Moreover, rhizosphere communities were assembled for the most part from soil. Interestingly, bacterial signatures are mainly linked from seed to seed, while fungal communities are shapesd by the soil and rhizosphere. Our findings provide a deep look into the rhizosphere and seed microbiome assembly of pumpkin-associated communities and represent the first steps into microbiome-driven breeding for plant-beneficial microbes.